Integrating merit systems and talent management: a legal-administrative framework for civil service professionalization - Jemmmy Dedi Rengku (Indonesian Institute For Counseling, Education and Therapy, 2026)
Bureaucratic reform requires a paradigm shift in Indonesia’s Civil Service (ASN) management from traditional personnel administration to meritocracy-based human resource governance and talent management. This study aims to analyze the legal framework and harmonization of the Merit System and Talent Management as instruments of legal development for establishing professional and high-integrity BerAKHLAK civil servants, while formulating policy strategies to address the gap between das sollen and das sein. This research employs a normative legal method using statutory, conceptual, and philosophical approaches, supported by an analysis of civil service policy implementation. The findings demonstrate that effective civil service governance requires integrating the Merit System as the normative foundation with Talent Management as the strategic mechanism for competency development, career advancement, leadership development, and succession planning. The effectiveness of this integration depends on harmonizing legal substance, institutional structure, and legal culture, reinforced by bureaucratic leadership, digital transformation, and the institutionalization of BerAKHLAK values. This study proposes the Harmonized Merit–Talent Governance Based on Legal Effectiveness, Legal Morality, Digital Governance, and Ethical Public Administration (HMTG–LED Model) as a new legal-administrative paradigm for strengthening professionalism, integrity, state capacity, and sustainable public service-oriented bureaucratic reform.